Ленин и мы: (материал к 121-й годовщине со дня рождения В. И. Ленина) / В. В. Трушков, Г. В. Мамичев - Трушков Виктор Васильевич (1991)
Экземпляры: КХ (20100428) / Инвентарный номер: 0287903 / Сис.шифр: 66.017 / Авт.знак: Т 80 / ГРНТИ: 03 / ББК: 63.3(2)6-8